Structural Functionalism Analysis On Children Labourers Phenomena In Jember Regency - Soepeno, Bambang; Suyadi, Bambang (International Journal of Scientific Research and Management (IJSRM), 2017)
The phenomenon of child labourer is a social fact that is difficult to eliminate in society (social system)because it is still functional for social structures such as family, business, and child labourer itself. Variouspolicies and regulations have been made by the government, but the implementation has not been effectivein dealing with child labourer issues. The aims of this study is to describe: (1) What is the reason parents donot ask their children to school, even though they are not burdened with the cost of education; (2) What isthe reason of the child involve into the world of work; And (3) What is the basic consideration of employersemploying children, despite being prohibited by the Manpower Act Number 13 Year 2003 and the Law ofthe Republic of Indonesia number 1 Year 2000. Based on the theory of structural functionalism, it explainedthat society is a social system consisting of parts or elements that are interrelated; united in order andbalance. Changes that occur in one part cause changes to other parts. The basic assumption is that anystructure in the social system is functional and can also be dis-functional to other social structures when thestructure has negative consequences. The certain consequences, both functional and dysfunctional have aparticular purpose and are recognized by the system element so that it is manifest (manifest function). Otherunrecognized elements are latency or having latency function. Through the perspective of the structuralfunctionalism theory, it can be explained that the phenomenon of child labourer is closely related to thefunctioning and dysfunction of social structures such as family, business, and child labourer itself, and in theprocess of interaction between structures within a particular social system of purpose. It is a manifest orlatency to the balance of the social system, so the phenomenon of child labourer persists and persists insociety. This research was conducted in Jember regency, precisely in 3 (three) sub districts, namelySumbersari, Kaliwates, and Patrang. The location is based on the consideration that there is an almost equalspread of labourers in the region because each region has the same potential for child labourers for variousreasons and considerations